A New Encryption Algorithm Using Symmetric Key Cryptography - Tumati, Gowtham; Rajesh, Yalamarthi; T, Manogna; Ram Kumar, J (International Journal of Engineering and Technology, 2018)
Cryptographic techniques are primarily divided into two categories and they are: Symmetric key type and Asymmetric key type. In Symmetric key cryptography, during the process of encryption and decryption, the same key will be used. This is a conventional method of Cryptography. This might cause some disadvantage and give way for attacks on the algorithm. So, for this reason, the next technique comes into play. In Asymmetric key cryptography, there is a usage of a pair of keys, one for the encryption process and another for decryption process. In this technique also, there is a slight disadvantage, since there is a possibility for attackers to guess the public key from the pair of keys, thereby posing a threat to the process to an extent. In this paper, we develop an algorithm with a simple yet efficient structure using Symmetric key cryptography that could possibly decrease the chance of attacks on the algorithm. Â Â